LOW RELIGIOSITY AS A CAUSE OF DRUG ABUSE IN ADOLESCENTS - Ismiati Ismiati (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2022)
AbstractThe problem of drug abuse is a big and serious threat to the moral destruction of the younger generation. The spread of drug abuse is almost unavoidable because it has become a global issue that has hit the world's population. This condition has caused anxiety for all parties, considering that the impact is very complex, both on individuals as users and on social communities. Efforts to eradicate drugs have often been carried out, but the number of perpetrators of drug abuse is still increasing and regardless of age. Adolescents are the group most at risk, given their age in transition. Drug abuse is a human behavior problem. Changes in behavior with religious values are needed by teenagers to become protectors from drug abuse. Strengthening religious values is needed for individuals who function as self-guards in thinking, behaving, and acting. Religiosity can affect every aspect of an individual's life, both physically and psychologically. Religion is more protective and preventive, especially for teenagers who are looking for self-identity, in order to avoid drug abuse behavior.Keywords: Religiosity, Drug Abuse, Adolescents